Validitas antropometri terhadap profil lipid pada pasien poli jantung RSUD Budhi Asih Jakarta Timur - Riva Octarina; Leni Sri Rahayu; Luthfiana Nurkusuma Ningtyas (ARGIPA (Arsip Gizi dan Pangan), 2020)
ABSTRACT Dyslipidemia is a major factor in cardiovascular disease which can cause atherosclerosis, ischemic stroke and peripheral arteries. Dyslipidemia can be predicted by anthropometric measurements. The purpose of this study was to determine the anthropometric measurements that have the highest validity in detecting lipid profiles compared to biochemical assessments in poly cardiac patients at Budhi Asih Regional Hospital, East Jakarta. Research conducted in cross sectional method with quota sampling. This study was conducted on 75 cardiac poly patients. Data was collected by anthropometric measurements of body weight, height, waist circumference and hip circumference. Data on lipid levels were obtained from hospital medical record data. The results showed the lipid profile of normal HDL patients (73.30%), Normal LDL (58.70%), Triglycerides normal (65.30%), Total cholesterol was not normal (52%). Anthropometric value of BMI Obesity (44%), high RLPP (85.3%) and high waist circumference (74.7%). The conclusion of the analysis showed that BMI had poor sensitivity and specificity values ​​for all lipid profiles (Se <60%). RLPP has a very good sensitivity value on all lipid profiles (se> 90%) but has an unfavorable specificity value (Sp <60%). Waist circumference has a relatively good sensitivity (Se> 70%) in LDL, Triglycerides and Total Cholesterol, whereas in HDL it is quite good (Se> 60%). But it has poor specificity (Sp <60%). The results of the three anthropometric measurements RLPP is the best measurement in detecting lipid profiles in cardiac poly patients compared with BMI and Waist Circumference. Keywords: Lipid Profile, BMI, RLPP, Waist Circumference, Sensitivity, Specificity